2022
DOI: 10.3390/biology11101473
|View full text |Cite
|
Sign up to set email alerts
|

The Blue Swimming Crab Portunus segnis in the Mediterranean Sea: Invasion Paths, Impacts and Management Measures

Abstract: Invasive alien species represent one of the main environmental emergencies and are considered by the scientific community as being among the leading causes of biodiversity loss on a global scale. Therefore, detecting their pathways, hotspot areas and invasion trends becomes extremely important also for management purposes. A systematic review on presence of Portunus segnis in the Suez Canal and Mediterranean Sea was carried out in order to study the invasion paths from its entry from the Red Sea into the Suez … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In our specific case, the establishment of a transnational observatory in the Strait of Sicily would allow better monitoring and management of bioinvasions between Tunisia, Italy and Malta. Previous experience has shown that the invasion of one species in one of these countries also subsequently occurs in the other countries, as was the case for e.g., Lagocephalus sceleratus [ 94 ] and Portunus segnis [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our specific case, the establishment of a transnational observatory in the Strait of Sicily would allow better monitoring and management of bioinvasions between Tunisia, Italy and Malta. Previous experience has shown that the invasion of one species in one of these countries also subsequently occurs in the other countries, as was the case for e.g., Lagocephalus sceleratus [ 94 ] and Portunus segnis [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…To define the expansion spatial and temporal dynamics, the cumulative number of records was calculated and the temporal pattern through the population's increasing rate over time based on evident slope changes of the cumulative curve of all occurrences was determined for both areas. Distribution maps were produced using the software QGIS (3.10.7‐A Coruña) considering only the year of the first record and not the number of specimens, to reduce the effect of possible preferential sampling (Castriota et al, 2022). The cumulative curve of O. cursor occurrences was calculated and divided into arbitrary intervals based on the most evident slope changes, corresponding to the phases of expansion (Olenin et al, 2017; Perzia et al, 2022), for each time interval identified, the equation of the regression line was calculated in order to obtain the different rate of occurrences increase over time.…”
Section: Methodsmentioning
confidence: 99%
“…Data from studies were extracted and organised into a geodatabase including the year of occurrence (if missing, the publication year was used), location, country, sea, geographic coordinates, method of detection (capture/observation), and references. According to Castriota et al [24], geographic coordinates were assigned a position accuracy value: 1-exact coordinates as reported in the bibliographic source or taken from a detailed map; 2-coordinates derived from a specific sighting/capture site, e.g., a city name; 3-coordinates derived from a generic sighting/capture site, e.g., a gulf name; and 4-coordinates derived from a highly generic location, e.g., a sea name.…”
Section: Callinectes Sapidus Invasion Historymentioning
confidence: 99%
“…In some areas, it has shown an invasive character [6,8,22] so considerable as to cause a negative socio-economic impact [22] and to require urgent action to contain the population. Mapping and monitoring the distribution of an invasive species is essential to understanding its spread and thus identifying areas of further expansion [23][24][25] in which to intervene with management actions [24]. From this perspective, occurrences of C. sapidus in the Mediterranean Sea and adjacent waters as well as in Northwest Europe are analysed in order to provide an overview of its spatial distribution and to identify the directional trends of its spread.…”
Section: Introductionmentioning
confidence: 99%